Remnants of a pandemic: Possibilities of educating in the face of loss and grief - Magalhaes, Silvana; da Luz Ferreira, Ananda; Tardim, Poliane; Wanderosck Toledo, Soraia; Mengali, Priscila; Custodio da Silva, Lubia; Rodrigues de Avellar Baptista, Leomar; Messa, Luciana (Guará Journal, 2022)
This article presents the university extension course Pedagogies do Esperançar: the art of educating in the face of loss and grief, whose main objective was to provide a space for sharing knowledge and welcoming regarding losses and mourning. This training prioritized awakening the educators’ watchful eye to the protagonism and narratives of children/adolescents about their processes of elaboration of losses. Offered by the Study and Research Group on Children, Cultures, Education and Society - GEPICES/CEFET/RJ in a remote environment, the course welcomed one hundred and thirty participants, who were able to highlight the need to talk about individual and collective pain; about death and grief. There were four virtual meetings that dealt with different aspects related to the theme. Through theoretical expositions, dialogic interactions, storytelling and narration, among other activities, spaces were created for acti-ve listening, that is, for the sharing of perceptions and feelings, which, based on the Sociology of Childhood, could be elabo-rated, resignified. In their testimonies, participants highlighted the importance of the proposed activities that dared to work on issues that contemporaneity insists on hiding. In the end, the perception that pain needs to be elaborated was confirmed.